The Initiative of the University of Gezira for Safe Motherhood and Childhood-Gezira State Sudan 2005-2011. - Hussien, Ismail Hassan; Abdella, Ahmed El Bashir; Habour, Ali Babikr; Ahmed Mirghani, Omer; El Sanousi, Mohamed; Eisa, El Fadil; Khalafalla, Somaya; Mohamed El Bashir, Ibtisam; Mohamed Osman, Osman Taha; Khalafalla Saied, Osman (Gezira Journal of Health Sciences, 2011)
The initiative was released by the vice chancellor of the University of Gezira in Feb 2004. Its main objective was to reduce the maternal mortality rate (MMR) and the newborn mortality rate (NMR) in the Gezira state by at least 50% within 5 years. The justifications, specific objectives, process of project design, strategies, implementation and methods of evaluation were described in the editorial article in the GJHS. Dec. 2006 Vol. (2) No (2). (1) The main objectives were upgrading of ante-natal care, intrapartum care, puerperal care and care of the newborn; with emphasis on the intrapartum care. The main strategies were strong political commitment and full partnership with the ministry of health (MOH) at all stages. By the end of 2011 and despite considerable challenges, objectives have been exceeded; the MMR dropped from 469 to 151/100,000 live births and the NMR dropped from 43 to 12/1000 live births Although the reduction in mortality was mainly due to the combined efforts of the initiative and the MOH, other effective factors-namely the overall socioeconomic development in the state must have contributed to that reduction. The main future plans of the initiative are: continue working on its objectives, conduct a comprehensive programme evaluation of the project and transfer the experience to other states in the Sudan. This article describes the main achievements of the initiative during the period 2005-2011: the implementation process, rural hospital development, upgrading of the village midwife (VMW), training, books issued by the initiative, information, evaluation and the future prospective.